317 Comparison of One-Day Combined Versus Staged Anterior and Posterior Cervical Decompression, Fixation and Fusion. (1st April 2022) - Mozaffari, Khashayar; Chalif, Eric; Stellon, Michael A.; Patrick, Hayes; Sparks, Andrew; Almeida, Neil; Rosner, Michael K.
Abstract : INTRODUCTION: Current management of cervical stenosis at times can involve both anterior and posterior decompression, stabilization and fusion. Although these procedures can be done in a combined or staged fashion, there is a scarcity of literature on this topic. METHODS: A retrospective cohort analysis was conducted on consecutive patients at a single institution between July 2015 and April 2019 who underwent either single day combined or separate day staged surgeries. Demographics, comorbidities, length of stay, perioperative complications, and inpatient medication use were compared between cohorts. Multivariable analysis was used to adjust for differences in demographics and other confounding covariates. RESULTS: 80 patients were analyzed (combined = 58, staged = 22). Comparing combined versus staged, there were no differences in baseline demographics. The administration of morphine equivalents was similar comparing combined and staged (569 vs 681 morphine equivalents, P = 0.66). Staged patients had significantly longer time in the operating room (7.2 vs 8.5 hours, P < 0.01) and longer duration of general anesthesia (6.7 vs 7.6 hours, P < 0.01). Incidence of post-operation delirium was significantly higher in the staged group (13.2% vs 50.0%), with an adjusted odds ratio of 23.3 (95% CI: 2.6 – 212.1; P < 0.01). Dysphagia was the most common post-operative complication seen in 43 patients (53.7%). Patients age > 60 had total length of stay 39.1% ± 15.0% longer than those age = 60 (multivariable adjusted mean ± standard error; P = 0.02). CONCLUSION: Staging anterior and posterior cervical decompression, stabilization and fusion is associated with longer usage of the operating room, longer duration of general anesthesia, and increased incidence of perioperative complications.